Analysis Of Theeffectof Inflation, BI Rate On Stock Price Volatility Through Currency Exchange As Intervening Variable In Consumer Goods Industry In IDX - Nely Supeni; Mustofa Mustofa (AGRIBEST, 2020)
This study to analyze the Influence of Inflation, BI Rate on Stock Price Volatility through Currency Exchange as Intervening Variables in Consumer Goods Industry on the Indonesia Stock Exchange. This type of research is a descriptive quantitative research that is quantitative research that describes the results of comparison in five companies in the Consumer Goods Industry sector are PT. Mayora Tbk, PT. Multi Bintang Indonesia Tbk, PT. Tempo Scan Pacific Tbk, PT. Ultrajaya, Tbk, PT. Unilever Tbk. Analysis of the data used is Path Analysis. Based on the analysis of the path of direct influence obtained the results of the study as follows: Currency Exchange has a significant and negative influence on Stock Price Volatility only at PT. Tempo Scan Pacific, Inflation has a significant and negative influence on Stock Price Volatility only at PT Unilever, while the other four companies have no significant effect. BI Rate is significant and negative towards Stock Price Volatility only at PT. Tempo Scan Pacific while the other four companies had no significant effect. The results of the analysis of indirect influence paths obtained that at PT. MayoraTbk, Currency Exchange is able to mediate the indirect effect between the BI Rate on Stock Price Volatility. At PT. Multi Bintang Indonesia Tbk, Currency Exchange is able to mediate the indirect effect between Inflation on Stock Price Volatility, and Currency Exchange able to mediate the indirect effect between BI Rate on Stock Price Volatility. In other companies, the Currency Exchange is unable to analyze the effect of the independent variable on the dependent variable